Effect of Dividend Payment on Stock Prices of Commercial Banks in Nepal: Panel Approach - Bhattarai, Yuga Raj (Economic Journal of Development Issues, 2018)
This study has examined the effect of dividend payment on stock prices of commercial banks in Nepal. The study has adopted causal comparative research design. The secondary data of six commercial banks were collected during 7 years (2010 to 2016) period. Data were analyzed using both descriptive and inferential statistics. From the empirical analysis this study found a significant positive relationship between share price and dividend payment. This study concludes that payment of dividend positively affect share price of Nepalese commercial banks. Economic Journal of Development Issues Vol. 21 & 22 No. 1-2 (2016) Combined Issue, Page: 55-68